2002
DOI: 10.1080/03079450120106642
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ochratoxin/aluminosilicate interaction on the tissues and humoral immune response of broilers

Abstract: This study aimed to evaluate the effect of dietary ochratoxin, in the presence or absence of aluminosilicate, on the histology of the bursa of Fabricius, liver and kidneys, and on the humoral immune response of broilers vaccinated against Newcastle disease virus. The exposure of birds to 2 p.p.m. ochratoxin, in the presence or absence of aluminosilicate, reduced their humoral immune response and the number of mitotic cells in the bursa. The relative weight of the livers of the birds exposed to this toxin was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
46
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 16 publications
14
46
1
Order By: Relevance
“…The significant decrease in antibody production against SRBCs and mean wattle thickness in response to PHA injection indicated a reduced humoral and cellular immune response in the OTA-treated groups. This agrees with previous reports showing that OTA fed to chickens at concentrations of 130 to 790 ppb, 5 parts/ 10 6 (Stoev et al ., 2000(Stoev et al ., , 2002; 2 parts/10 6 (Singh et al ., 1990;Santin et al ., 2002) or 4 parts/10 6 (Elkady, 1993); reduced either humoral or cellular immune response, or both. Furthermore, OTA fed to broilers alone (4 parts/ 10 6 ) decreased humoral immunity, and in combination with aflatoxin (2 parts/10 6 ) decreased humoral and cellular immunity (Verma et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The significant decrease in antibody production against SRBCs and mean wattle thickness in response to PHA injection indicated a reduced humoral and cellular immune response in the OTA-treated groups. This agrees with previous reports showing that OTA fed to chickens at concentrations of 130 to 790 ppb, 5 parts/ 10 6 (Stoev et al ., 2000(Stoev et al ., , 2002; 2 parts/10 6 (Singh et al ., 1990;Santin et al ., 2002) or 4 parts/10 6 (Elkady, 1993); reduced either humoral or cellular immune response, or both. Furthermore, OTA fed to broilers alone (4 parts/ 10 6 ) decreased humoral immunity, and in combination with aflatoxin (2 parts/10 6 ) decreased humoral and cellular immunity (Verma et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…OTA was detrimental also to quail (Farshid & Rajan, 1996) and turkey immunity (Dwivedi & Burns, 1985). Suppression of humoral and cellular immunity by OTA reduces the immune response of chickens to vaccination against Newcastle disease virus strain B1 (Stoev et al, 2000(Stoev et al, , 2002 or LaSota strain (Santin et al ., 2002), and allows development of secondary bacterial infections (Kumar et al ., 2003(Kumar et al ., , 2004 Two findings that were reported in this study, a reduced leucocyte count and thymus weight, implied that the functioning of the immune system is altered. Regression of other lymphoid organs, the spleen and bursa of Fabricius, were reported during ochratoxicosis (Dwivedi & Burns, 1984a;Singh et al ., 1990;Elkady, 1993;Stoev et al ., 2000Stoev et al ., , 2002Kumar et al ., 2004;Verma et al ., 2004) and was found to be accompanied by a decrease in the number of lymphoid cells present (Peckam et al ., 1971;Stoev et al ., 2000Stoev et al ., , 2002Kumar et al, 2004) and in the immunoglobulin-containing cells (Dwivedi & Burns, 1984b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, feeding OTA-contaminated diet at 2.6 mg/Kg feed for 90 days resulted in the significant depression in the levels of CD4 + or CD8 + cell types and in the mitogenic responses to Concanavalin A (Thuvander et al, 1995). In an experiment, feeding OTA at 2 mg/Kg diet to broiler chicks for 42 days, Santin et al (2002) reported significantly lower humoral immune responses (as demonstrated by decreased titers to Newcastle disease virus). Depressed humoral and cell-mediated immune responses were also noted by Sawale et al (2009) in laying hens that had been maintained on an OTA-contaminated diet (at 1 ppm) for 60 days.…”
Section: Research Articlementioning
confidence: 99%
“…Though the specific cellular and molecular mechanisms underlying the immunotoxic effects of OTA are not known, inhibition of protein, DNA, and RNA synthesis, as well as degenerative/apoptotic changes in key immune system cells due to ochratoxicosis provide significant clues to determining how OTA mediates its effects (Sharma, 1993;Santin et al, 2002;Rocha et al, 2005;Al-Anati and Petzinger, 2006). In mice, feeding OTA-contaminated diet at 2.6 mg/Kg feed for 90 days resulted in the significant depression in the levels of CD4 + or CD8 + cell types and in the mitogenic responses to Concanavalin A (Thuvander et al, 1995).…”
Section: Research Articlementioning
confidence: 99%